Development and Effectiveness of SKIRD Media Integrated with the ONCE Model to Enhance Elementary Students Creativity in Writing Fiction Texts - Dani Darmawan; Henny Dewi Koeswanti; Wahyu Purwiyastuti (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study aims to develop and examine the effectiveness of SKIRD (Skill Card) learning media integrated with the ONCE (Observe, Analyze, Verify, Evaluate) learning model in enhancing elementary school students’ creativity in writing fictional texts. The study addresses the need for innovative instructional media that systematically support creative writing processes at the primary education level. Methodology: This study employed a quantitative research and development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). Data were collected through expert validation to assess media feasibility and creativity assessment rubrics administered during pretest and posttest activities. The data were analyzed using descriptive and inferential statistical techniques to evaluate the effectiveness of the developed learning media. Main Findings: The results show that the SKIRD learning media achieved a high level of feasibility based on expert validation. Statistical analysis of pretest and posttest scores indicates a significant improvement in students’ creativity in writing fictional texts (p < 0.05). The implementation of SKIRD integrated with the ONCE model enhanced students’ fluency, flexibility, originality, and elaboration in developing fictional narratives. Novelty/Originality of this study: The novelty of this study lies in the integration of SKIRD card-based learning media with the ONCE reflective learning model to systematically guide elementary students through the stages of creative writing. This study offers a structured instructional framework that links media use with reflective learning processes to enhance creativity in writing fictional texts at the elementary level.